Holocene progradation and retrogradation of the Central Texas Coast regulated by alongshore and cross‐shore sediment flux variability. (15th December 2020) - Odezulu, Christopher I.; Swanson, Travis; Anderson, John B.
Abstract: Fifteen transects of sediment cores located off the central Texas coast between Matagorda Peninsula and North Padre Island were investigated to examine the offshore record of Holocene evolution of the central Texas coast. The transects extend from near the modern shoreline to beyond the toe of the shoreface. Lithology, grain size and fossil content were used to identify upper shoreface, lower shoreface, ebb‐tidal delta and marine mud lithofacies. Interpretations of these core transects show a general stratigraphic pattern across the study area that indicates three major episodes of shoreface displacement. First, there was an episode of shoreface progradation that extended up to 5 km seaward. Second, an episode of landward shoreline displacement is indicated by 3–4 km of marine mud onlap. Third, the marine muds are overlain by shoreface sands, which indicates another episode of shoreface progradation of up to 5 km seaward. Radiocarbon ages constrain the onset of the first episode of progradation to ca 6.5 ka, ending at ca 5.0 ka when the rate of sea‐level rise slowed from an average rate of 1.6–0.5 mm/yr. Results from sediment budget calculations and sediment transport modelling based on reasonable estimates of an ancient shoreline shape and wave climate indicate that the first progradation was a result of sand supplied from erosion of the offshore Colorado and Rio Grande deltas. The transgressive phase occurred between ca 4.9 ka and ca 1.6 ka and coincided with a major expansion of the Texas Mud Blanket, which resulted in burial of offshore sand sources and the shoreface being inundated with mud. The second, more recent episode of shoreface progradation began ca 500 years ago with a maximum rate of ca 6 m/yr. This most recent change signals a healing phase of coastal evolution from the late Holocene transgressive event. Currently, the shoreline along the central Texas coast is retreating landward at an average rate of 0.30 m/yr, indicating that the second progradation event has ended. Abstract : Sediment cores from the central Texas coast were investigated to examine the offshore record of Holocene evolution of the central Texas coast. Two episodes of shoreface progradation of up to 5 km separated by 3–4 km of marine mud onlap were observed. Results from sediment budget calculations and sediment transport modelling indicate that the first progradation was as a result of increased sand supply from erosion of the offshore Colorado and Rio Grande deltas. The transgressive phase occurred between ca 4.9 ka and ca 1.6 ka and coincided with a major expansion of the Texas Mud Blanket.